Causal Relationship between the Right Auditory Cortex and Speech-Evoked Envelope-Following Response: Evidence from Combined Transcranial Stimulation and Electroencephalography. (23rd August 2021) - Mai, Guangting; Howell, Peter
Abstract: Speech-evoked envelope-following response (EFR) reflects brain encoding of speech periodicity that serves as a biomarker for pitch and speech perception and various auditory and language disorders. Although EFR is thought to originate from the subcortex, recent research illustrated a right-hemispheric cortical contribution to EFR. However, it is unclear whether this contribution is causal. This study aimed to establish this causality by combining transcranial direct current stimulation (tDCS) and measurement of EFR (pre- and post-tDCS) via scalp-recorded electroencephalography. We applied tDCS over the left and right auditory cortices in right-handed normal-hearing participants and examined whether altering cortical excitability via tDCS causes changes in EFR during monaural listening to speech syllables. We showed significant changes in EFR magnitude when tDCS was applied over the right auditory cortex compared with sham stimulation for the listening ear contralateral to the stimulation site. No such effect was found when tDCS was applied over the left auditory cortex. Crucially, we further observed a hemispheric laterality where aftereffect was significantly greater for tDCS applied over the right than the left auditory cortex in the contralateral ear condition. Our finding thus provides the first evidence that validates the causal relationship between the right auditory cortex and EFR.